Libyan EFL Teachers’ Perceptions of Written Corrective Feedback Methods: A Qualitative Exploration in Tripoli University - Bilban, Alhadi (JOLLT Journal of Languages and Language Teaching, 2026)
Writing in English is an essential skill for ESL learners, and qualified teachers play a key role in providing effective written corrective feedback (WCF). While much research has examined the general effectiveness of WCF, less attention has been given to teachers’ perceptions of WCF methods and expected outcomes. This qualitative study investigated Libyan university English teachers’ perceptions of their knowledge, experience, and training related to WCF. Data were collected through semi-structured interviews with four participants and were analyzed thematically to identify patterns in their beliefs and practices. Findings revealed that participants held clear views on providing writing corrections but showed inconsistencies in their understanding and use of specific WCF types, often due to limited training. These results underscore the need for targeted professional development programs that help teachers apply various feedback methods effectively. Such initiatives can strengthen EFL pedagogy by aligning teacher feedback practices with students’ learning needs and institutional writing objectives. Future research may explore the long-term effects of WCF on learners’ writing proficiency and feedback retention.